Identifikasi Faktor Signifikan Yang Mempengaruhi Kinerja Kontraktor Kategori Besar Dan Menengah Dalam Berkompetisi Di Pasar Global Berdasarkan Analitycal Hierarchy Process (AHP) Di Kota Padang Tahun 2018 - Mirza, Febtrinal; Malik, Alfian; Iriana, Rian Tri Komara (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
In the era of globalization as it is today, competition between actors in the field of construction is developing very rapidly. The rapid development of the construction world in Indonesia has not been accompanied by an increase in the quality and performance of construction services companies. In accordance with ISO 9004 of 2008, that the ongoing success of a company is achieved with its ability to meet customer needs and expectations with effective management and through corporate environmental awareness. This study aims to identify internal factors and analyze levels that significantly affect the performance of contractors in competing in the global market in the city of Padang and map the level of readiness of contractors using the Analytical Hierarchy Process (AHP) method. Primary data in this study were obtained from questionnaires and interviews with construction service companies, especially medium and large qualification contractor companies. and secondary data obtained from the LPJK website and based on ISO 9004. Based on the identification of the internal factors of the companies, it was found the final result that the significant internal factors affected the performance of construction service companies in large levels company in competing the global market in sequence are : company management, company finance, human resource, strategy company and information technology company. While the significant internal factors in medium levels company in sequence are : company finance, company management, human resource, strategy company and information technology company. The readiness of construction service company at the large level in Padang is 88.5% and the medium level is 86.5%. This value indicates that readiness level is greater than 50% which means that the construction service companies in Padang ready to compete in global market.Keywords: Identification, Significant Factors, AHP, Internal Company, Global Market.